Finite Element Analysis of Spur Gear Set in Noodles-making Machine Using Different Materials and Face Widths - Thin, Po Po; Win, Htay Htay; Soe, Aung Kyaw; Latt, Aung Ko (The Indonesian Journal of Computer Science, 2024)
This paper focuses on the design and structural analysis of a spur gear set for a noodles-making machine by changing three different materials (ASTM A 536, ASTM A 220, and AISI 1020) and gear face widths. Gear corrosion occurs at contact points as a result of bending stress and contact stress. This is the major source of the gear failure of the noodles-making machine. Pitch diameters of 50mm and modules of 5mm spur gears are selected in the design of the roller gear set. In theoretical analysis, the AGMA contact stress equation was used based on the Hertzian theory. The minimum von Mises stress and effective strain are found on AISI 1020 carbon steel by using ANSYS 17.0 software. In this paper, von Mises stress and effective strain are analyzed by changing the face widths of spur gear set to 8mm, 10mm, 12mm, 14 mm, and 16mm and using finite element analysis (FEA). Although all face widths are safe for this design, 12mm is chosen in this paper due to power consumption and strength points of view.